Core-shell nanoparticle / dynamic polyimine composite material for synergistically toughening and increasing glass transition temperature
By combining polymer core-shell nanoparticles with dynamic polyimine composite materials, toughened polyimine composite materials are prepared by using phase transfer, which solves the problem of insufficient mechanical properties of dynamic polymers and achieves significant improvement in performance.
Patent Information
- Application Number
- CN202411690337.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Dynamic polymers have shortcomings in mechanical properties and temperature resistance levels, which limit their application potential.
The formulation and preparation method of polymer core-shell nanoparticles and dynamic polyimine composite materials are adopted, and the core-shell nanoparticles are introduced through phase transfer to form a toughened polyimine composite material.
It significantly improves the fracture toughness, glass transition temperature and hydrophobicity of the composite material, and improves the overall performance of the material.
Smart Images

Figure CN119410144A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of synthesis of dynamic polymer composite materials, in particular to the formulation and preparation of a polymer core-shell nanoparticle modified polyimine composite material. Background Art
[0002] Dynamic covalent cross-linked polymers are a class of polymers with special properties. Their characteristics are that their cross-linked structures are dynamic and can be broken and reorganized under specific conditions. This gives these polymers some unique properties, such as self-healing, shape memory, and reprocessability. Among the many dynamic chemical bonds, imine bonds are a type of reversible dynamic covalent bonds. Their polymerization conditions are mild, and changes in external temperature, humidity, and acidity and alkalinity can cause the imine bonds to dissociate or non-dissociate in a dynamic manner. Reversible cross-linked polymers based on imine bonds show interesting application potential and high recycling value in many fields. Although dynamic polyimine cross-linked polymers have proven many advantages, their dynamic nature usually also makes the polymers face environmental stability challenges, including mechanical properties, glass transition temperature, and hydrophobicity, which greatly limits the application potential of dynamic covalent cross-linked polymers.
[0003] Polymer core-shell nanoparticles are a type of structured and functionalized composite particles, which are composed of at least two substances with different chemical compositions and show a double-layer or multi-layer structure. As a structured composite particle, the double-layer or multi-layer structure of polymer core-shell nanoparticles enables it to have multiple functions and applications. By adjusting the composition, size and morphology of the core and shell, it is possible to achieve precise control of the properties of polymer core-shell nanoparticles, thereby playing an important role in the fields of biomedicine, catalysts, sensors, energy storage, etc. However, the formulation and application of polymer core-shell nanoparticles in the field of dynamic polymers have not been reported. The present invention combines polymer core-shell nanoparticles with dynamic polyimine, and the prepared polymer core-shell nanoparticle toughened polyimine composite material has obvious synergistic toughening and glass transition temperature improvement effects compared to the polyimine matrix, and is also improved in terms of hydrophobicity. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of insufficient mechanical properties and insufficient temperature resistance of dynamic polymers and to expand their application fields. To this end, we provide a formula and preparation method of a polymer core-shell nanoparticle toughened polyimide composite material.
[0005] The purpose of the present invention is achieved through the following technical solutions: A core-shell nanoparticle / dynamic polyimide composite material with synergistic toughening and glass transition temperature enhancement specifically includes the following preparation steps and formula design: Step S1: Add terephthalaldehyde to an organic solvent, stir for a certain time at a certain temperature, so that the terephthalaldehyde is completely dissolved in the organic solvent. S2: Add a diamine monomer containing a fluorene group to the solution, stir and dissolve at a certain temperature. S3: Add polymer core-shell nanoparticles in a certain form and a certain proportion to the solution and disperse and stir evenly. S4: Finally, add a triamine crosslinking agent to form a dynamic crosslinking network. After continuing to stir for a certain time, pour the solution into a glass culture dish, place it in a blast oven to dry, and then place it in a vacuum oven for post-curing and cross-linking to obtain a core-shell toughened polyimide composite material.
[0006] Further: the organic solvent in step S1 is one or a mixture of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide, and chloroform, the certain temperature is 0-40°C, and the certain time is 5-30 min.
[0007] Further: the fluorene-containing diamine in step S2 is one or more of 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(3-fluoro-4-aminophenyl)fluorene, and 9,9-bis[4-(4-aminophenoxy)phenyl]fluorene. The certain temperature is 0-40°C, the mass of the added core-shell particles is 5-40% of the theoretical mass of the synthesized polyimine, and the certain time is 0.5-3 h.
[0008] Further: The method for preparing a polymer core-shell nanoparticle toughened polyimide composite material according to claim 1 is characterized in that: the polymer core-shell in step S3 is a composite of polymethyl methacrylate as a shell, polybutyl acrylate as a core, a polymer copolymerized by butyl acrylate and methyl methacrylate as a shell, octamethylcyclotetrasiloxane as a core, or one or more of Japanese Zhongyuan M722, M521, and MX-125 polymer core-shell. The doping state of the micro-nano core-shell particles is a powder after the emulsion is demulsified and dried, or a flocculent after the emulsion is phase-inverted. The doping ratio of the polymer core-shell particles is 0.01%-50%.
[0009] Further: the triamine crosslinking agent in step S4 is one or a mixture of tris(2-aminoethyl)amine, trimethylolpropane tripropylene glycol ether (amino-terminated), and the stirring time is 30-300 s. The temperature of the blast drying oven is 60-80°C, and the drying time is 12-72 h. The temperature of the vacuum oven is 100-160°C, and the curing time is 0.5-5 h.
[0010] The polyimine composite material obtained by the above preparation method is a polyimine composite material toughened by polymer core-shell nanoparticles. Compared with the uncompounded polyimine material, the polyimine composite material toughened by polymer core-shell nanoparticles has been significantly improved in toughness, glass transition temperature, and hydrophobicity, and has outstanding substantial characteristics and significant progress.
[0011] Compared with the prior art, the present invention has the following advantages and beneficial effects: The phase transfer method is used to introduce polymer core-shell nanoparticles. Compared with traditional blending methods, the phase transfer method can better disperse the core-shell particles with materials such as polymers, avoiding the problem of particle aggregation and accumulation. The phase transfer method is often carried out under mild reaction conditions, such as room temperature and without high pressure. Compared with the traditional blending method that requires higher temperature or high shear force conditions, the phase transfer method has lower requirements for the thermal stability of the reaction substances. In addition, the phase transfer method has strong selectivity and controllability, and can regulate particle size, dispersion, morphology and other characteristics. This selectivity and controllability make the phase transfer method have advantages in the fields of nanoparticles, polymer composites, etc.
[0012] The polymer core-shell nanoparticle toughened polyimide composite material prepared by the present invention has improved fracture toughness, glass transition temperature and hydrophobicity. The fracture toughness is 3.3 MJ / m compared to the polyimide resin matrix. 3 Increased to 5.2 MJ / m 3 Compared with the data of the comparative example, the glass transition temperature increases from 80°C to 105°C, an increase of 25°C, and the water contact angle also increases by about 10 degrees. These properties have significant improvements. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a photo of the core-shell emulsion prepared in Example 1 after phase transfer.
[0014] Figure 2 This is a real photo of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 1.
[0015] Figure 3 This is the infrared characteristic peak spectrum of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Examples 1, 2 and 3. 1639 cm -1 The characteristic peaks of the dynamic imine bond at 1560 cm -1 The characteristic peaks of aromatic benzene rings at 1750 cm -1 The C=O stretching vibration peak at proves the introduction of core-shell particles.
[0016] Figure 4The water contact angle of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Examples 1, 2 and 3 varies with time. Compared with the water contact angle of the polyimide resin matrix of the comparative example, the water contact angle of the composite material increases by about 10°.
[0017] Figure 5 The following are scanning calorimetry (DSC or DMA) graphs of the polymer core-shell nanoparticle toughened polyimine composites prepared in Examples 1, 2 and 3. Compared with the polyimine resin matrix of the comparative example before compounding, the glass transition temperatures of the polyimine composites of Examples 1, 2 and 3 after compounding were significantly increased by 22°C, 23°C and 25°C, respectively.
[0018] Figure 6 The stress-strain performance comparison diagram of the polymer core-shell nanoparticle toughened polyimine composites prepared in Examples 1, 2 and 3. Compared with the polyimine resin of the comparative example before compounding, the fracture toughness of the polyimine composite films of Examples 1, 2 and 3 after compounding increased by 9%, 10% and 58% respectively. DETAILED DESCRIPTION
[0019] In order to better understand the present invention, the technical solution of the present invention is further described below in conjunction with embodiments and drawings, but the implementation mode of the present invention is not limited thereto. Example
[0020] 0.805 g of terephthalaldehyde (6 mmol) and 16.8 g of N-methylpyrrolidone solvent were added to a 100 mL beaker. After magnetic stirring at room temperature (25 °C) for 10 min, terephthalaldehyde was completely dissolved. Then 1.045 g of 9,9-bis(4-aminophenyl)fluorene (2 mmol) was added and stirred for 10 min before dissolving. Finally, 0.292 g of crosslinker tris(2-aminoethyl)amine (2 mmol) and 2 g of N-methylpyrrolidone were added to the beaker and stirred at room temperature for 1 min. Then, the mixture was poured into a glass Petri dish and placed in a 70 °C oven to evaporate the solvent for 48 h. Then, the mixture was taken out and placed in a 150 °C vacuum oven for curing for 1 h to obtain a polyimide resin matrix (Cardo-DPI).
[0021] Figure 3 The infrared characteristic peak spectrum of the polymer core-shell nanoparticle modified polyimine composite material prepared in the comparative example.
[0022] Figure 4 This is a bar graph showing the change in water contact angle over time for the polymer core-shell nanoparticle modified polyimine composite material prepared in the comparative example.
[0023] Figure 5The following is a scanning calorimetry (DSC or DMA) diagram of the polymer core-shell nanoparticle modified polyimine composite material prepared in the comparative example.
[0024] Figure 6 The stress-strain curve of the polymer core-shell nanoparticle modified polyimine composite material prepared in the comparative example. Example 1
[0025] Phase transfer of core-shell emulsion: Add 6.8 g of butanone (MEK) to a beaker, then add 5 g of core-shell emulsion and stir evenly (10 min). Then, add 8 g of deionized water and continue stirring for 30 min. Then, let it stand for 30 min and find that the layers are separated. Filter the lower water layer to obtain the polymer core-shell nanoparticles after phase transfer.
[0026] Figure 1 This is a photo of the core-shell emulsion prepared in Example 1 after phase transfer.
[0027] 0.805 g of terephthalaldehyde (6 mmol) and 16.8 g of N-methylpyrrolidone solvent were added to a 100 mL beaker. After magnetic stirring at room temperature (25 °C) for 10 min, terephthalaldehyde was completely dissolved. Then 1.045 g of 9,9-bis(4-aminophenyl)fluorene (2 mmol) was added and stirred for 10 min to dissolve. Then 0.193 g of core-shell particles (10 wt%) after phase transfer was added and stirred for 2 h. Finally, 0.292 g of crosslinker tri(2-aminoethyl)amine (2 mmol) and 2 g of N-methylpyrrolidone were added to the beaker and stirred for 1 min at room temperature. Then, the mixture was poured into a glass Petri dish and placed in a 70 °C oven to evaporate the solvent for 48 h. Then, the mixture was taken out and placed in a 150 °C vacuum oven for curing for 1 h. Finally, a polymer core-shell nanoparticle toughened polyimide composite material (Cardo-DPI+10% CS) was obtained.
[0028] Figure 2 This is a real photo of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 1.
[0029] Figure 3 This is the infrared characteristic peak spectrum of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 1.
[0030] Figure 4 This is a bar graph showing the change in water contact angle of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 1 over time.
[0031] Figure 5 This is a scanning calorimetry (DSC or DMA) diagram of the polymer core-shell nanoparticle toughened polyimine composite material prepared in Example 1.
[0032] Figure 6 This is a stress-strain curve of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 1. Example 2
[0033] The phase transfer process of polymer core-shell nanoparticles is the same as that in Example 1.
[0034] 0.805 g of terephthalaldehyde (6 mmol) and 18.8 g of N-methylpyrrolidone solvent were added to a 100 mL beaker. After magnetic stirring at room temperature (25 °C) for 10 min, terephthalaldehyde was completely dissolved. Then 1.045 g of 9,9-bis(4-aminophenyl)fluorene (2 mmol) was added and stirred for 10 min to dissolve. Then 0.385 g of core-shell particles (20 wt%) after phase transfer were added and stirred for 2 h. Finally, 0.292 g of crosslinker tri(2-aminoethyl)amine (2 mmol) and 2 g of N-methylpyrrolidone were added to the beaker and stirred for 1 min at room temperature. Then, the mixture was poured into a glass Petri dish and placed in a 70 °C oven to evaporate the solvent for 48 h. Then, the mixture was taken out and placed in a 150 °C vacuum oven for curing for 1 h. Finally, a polymer core-shell nanoparticle toughened polyimide composite material (Cardo-DPI+20% CS) was obtained.
[0035] Figure 3 This is the infrared characteristic peak spectrum of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 2.
[0036] Figure 4 This is a bar graph showing the change in water contact angle of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 2 over time.
[0037] Figure 5 This is a scanning calorimetry (DSC or DMA) diagram of the polymer core-shell nanoparticle toughened polyimine composite material prepared in Example 2.
[0038] Figure 6 This is a stress-strain curve of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 2. Example 3
[0039] The phase transfer process of polymer core-shell nanoparticles is the same as that in Example 1.
[0040] 0.805 g of terephthalaldehyde (6 mmol) and 20.5 g of N-methylpyrrolidone solvent were added to a 100 mL beaker. After magnetic stirring at room temperature (25 °C) for 10 min, terephthalaldehyde was completely dissolved. Then 1.045 g of 9,9-bis(4-aminophenyl)fluorene (2 mmol) was added and stirred for 10 min to dissolve. Then 0.578 g of core-shell particles (20 wt%) after phase transfer were added and stirred for 2 h. Finally, 0.292 g of crosslinker tri(2-aminoethyl)amine (2 mmol) and 2 g of N-methylpyrrolidone were added to the beaker and stirred for 1 min at room temperature. Then, the mixture was poured into a glass Petri dish and placed in a 70 °C oven to evaporate the solvent for 48 h. Then, the mixture was taken out and placed in a 150 °C vacuum oven for curing for 1 h. Finally, a polymer core-shell nanoparticle toughened polyimide composite material (Cardo-DPI+30% CS) was obtained.
[0041] Figure 3 This is the infrared characteristic peak spectrum of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 4.
[0042] Figure 4 This is a bar graph showing the change in water contact angle of the polymer core-shell nanoparticle toughened polyimine composite material prepared in Example 4 over time.
[0043] Figure 6 This is a stress-strain curve of the polymer core-shell nanoparticle toughened polyimide composite material prepared in Example 4. Example 4
[0044] The phase transfer process of polymer core-shell nanoparticles is the same as that in Example 1.
[0045] 0.805 g of terephthalaldehyde (6 mmol) and 17.9 g of N-methylpyrrolidone solvent were added to a 100 mL beaker. After magnetic stirring at room temperature (25 °C) for 10 min, terephthalaldehyde was completely dissolved. Then 1.045 g of 9,9-bis(4-aminophenyl)fluorene (2 mmol) was added and stirred for 10 min to dissolve. Then 0.289 g of core-shell particles (15 wt%) after phase transfer was added and stirred for 2 h. Finally, 0.292 g of crosslinker tri(2-aminoethyl)amine (2 mmol) and 2 g of N-methylpyrrolidone were added to the beaker and stirred for 1 min at room temperature. Then, the mixture was poured into a glass Petri dish and placed in a 70 °C oven to evaporate the solvent for 48 h. Then, the mixture was taken out and placed in a 150 °C vacuum oven for curing for 1 h. Finally, a polymer core-shell nanoparticle toughened polyimide composite material (Cardo-DPI+15% CS) was obtained. Example 5
[0046] 0.805 g of terephthalaldehyde (6 mmol) and 17.9 g of N-methylpyrrolidone solvent were added to a 100 mL beaker. After magnetic stirring at room temperature (25 °C) for 10 min, terephthalaldehyde was completely dissolved. Then 1.045 g of 9,9-bis(4-aminophenyl)fluorene (2 mmol) was added and stirred for 10 min to dissolve. Then 0.193 g of core-shell powder (10 wt%) after emulsion demulsification was added and continued to stir for 2 h. Finally, 0.292 g of crosslinker tri(2-aminoethyl)amine (2 mmol) and 2 g of N-methylpyrrolidone were added to the beaker and continued to stir at room temperature for 1 min. Then it was poured into a glass Petri dish and placed in a 70 °C oven to evaporate the solvent for 48 h. Then it was taken out and placed in a 150 °C vacuum oven for curing for 1 h. Finally, a polymer core-shell nanoparticle toughened polyimide composite material (Cardo-DPI+15% CS) was obtained.
Claims
1. A method for preparing a polymer core-shell nanoparticle toughened polyimide composite material, characterized in that: The specific steps include: S1: adding terephthalaldehyde to an organic solvent, stirring for a certain time at a certain temperature to completely dissolve the terephthalaldehyde in the organic solvent; S2: adding a fluorene-containing diamine monomer into the solution and stirring and dissolving it at a certain temperature; S3: polymer core-shell nanoparticles are added to the solution in a certain form and proportion and dispersed and stirred evenly; S4: Finally, a triamine crosslinking agent is added to form a dynamic crosslinking network. After continuing to stir for a certain period of time, the solution is poured into a glass culture dish, placed in a forced air oven for drying, and then placed in a vacuum oven for post-curing and crosslinking to obtain a core-shell toughened polyimide composite material.
2. The method for preparing the polymer core-shell nanoparticle toughened polyimide composite material according to claim 1, characterized in that: In step S1, the organic solvent is one of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide, and chloroform, or a mixture of the above, the certain temperature is 0-40°C, and the certain time is 5-30 minutes.
3. The method for preparing the polymer core-shell nanoparticle toughened polyimide composite material according to claim 1, characterized in that: In step S2, the fluorene-containing diamine is one or more of 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(3-fluoro-4-aminophenyl)fluorene, and 9,9-bis[4-(4-aminophenoxy)phenyl]fluorene. The certain temperature is 0-40°C, the mass of the added core-shell particles is 5-40% of the theoretical mass of the synthesized polyimine, and the certain time is 0.5-3 h.
4. The method for preparing the polymer core-shell nanoparticle toughened polyimide composite material according to claim 1, characterized in that: S3 The polymer core-shell is a composite of polymethyl methacrylate as the shell, polybutyl acrylate as the core, a polymer copolymerized from butyl acrylate and methyl methacrylate as the shell, octamethylcyclotetrasiloxane as the core, or one or more of Japan's Kanebashi M722, M521, and MX-125 polymer core-shells; the doping state of the micro-nano core-shell particles is a powder after emulsion demulsification and drying, or a flocculent after phase inversion of the emulsion; the doping ratio of the polymer core-shell particles is 0.01%-50%.
5. The method for preparing the polymer core-shell nanoparticle toughened polyimide composite material according to claim 1, characterized in that: The triamine crosslinking agent in S4 is one of tris(2-aminoethyl)amine and trimethylolpropane tripropylene glycol ether (amino-terminated) or a mixture of the two, and the stirring time is 30-300 s. The temperature of the blast drying oven is 60-80°C, and the drying time is 12-72 h. The temperature of the vacuum oven is 100-160°C, and the curing time is 0.5-5 h.
6. A polymer core-shell nanoparticle modified polyimine composite material obtained by the preparation method according to any one of claims 1 to 5.
7. The polymer core-shell nanoparticle toughened polyimide composite material according to claim 6, characterized in that: Compared with uncompounded polyimine materials, polyimine composites toughened by polymer core-shell nanoparticles have improved toughness, glass transition temperature and hydrophobicity, with outstanding substantial characteristics and significant progress.
Citation Information
Patent Citations
Preparation method of copolymerized polyimine dynamic polymer film containing large-volume side group
CN115819699A
Preparation method of degradable and recoverable copolymerized polyimine film based on large-volume fluorenyl
CN117946354A
Toughening and enhancing type nano core-shell particle toughening agent as well as preparation method and application thereof
CN118271792A
Preparation method of epoxy resin flexibilizer and application of obtained product
CN118344707A
Polyrotaxane additives for rigid polymers
US20230159753A1